Aging and Rutting Resistance by Using Complex Process for Mixing Crumb Rubber Modifier at Intermediate and High Temperatures - Ismail Bakheit Eldouma; suliman Badawi Ahmed; Sani Aliyu; Dewi Amalia; putu tantri kumalasari (Potensi: Jurnal Sipil Politeknik, 2026)
To mitigate the environmental impacts of road construction and maintenance, it is essential to identify solutions that enhance pavement performance through improved ageing resistance while minimizing adverse ecological effects. This study assessed how the complex modified dry procedure for mixing crumb rubber modifier at high temperatures affected the material's resilience to rutting and ageing. To guarantee the uniformity of the CRM maintained throughout this study, only one batch of crumb rubber was used. The tire rubber powder size utilized was passed through a sieve No. 70 mesh (212 µm), and retained on a sieve No. 80 mesh (180 µm). For this purpose, improved asphalt mixtures were designed and tested using several methods, including wheel-tracking tests, thin-film oven tests (TFOT), Marshall stability, indirect tensile strength, and pressure-aging-vessels (PAV) to simulate ageing conditions. Three crumb rubber blending techniques were carefully assessed in terms of stability, indirect tensile strength, rutting, moisture susceptibility, and ageing resistance. Five types of rubberized bitumen blended specimens (e.g., 0, 5%, 10%, 15%, and 20% by weight of net asphalt) were prepared at high temperatures. The ageing and rutting resistance of crumb rubber modifiers was investigated, and superior results were obtained for improving the mechanical properties of asphalt mixtures.